Exploring Critical Thinking Activities In Pre-Service English Teachers’ Lesson Plans - Alfian Alfian; Yona Dwi Yolanda (English Education Study Program Faculty of Teacher Training and Education, 2022)
The objective of this research is to explore to what extent pre-service teacher uses critical thinking activities in their lesson plans. The research carried out pre-service teachers’ lesson plans during teaching practicum. The lesson plans analyzed are made by the pre-service teacher for the second grade in secondary school. The research embodied content analysis research to find out the critical thinking activities in pre-service teachers’ lesson plans. The results show nine of the eleven lesson plans have used thinking activities. The critical thinking activities contained in the lesson plan are essays, group discussions, student presentations, and analytical questions in their lesson plans. In conclusion, pre-service teachers provided various activities that contain critical thinking in their lesson plans with percentage 82%.